The effect of fungicide sprays on powdery mildew and rust and yield of sugar beet in Denmark. (September 2020) - Heick, Thies Marten; Hansen, Anne Lisbet; Munk, Lisa; Labouriau, Rodrigo; Wu, Karl; Jørgensen, Lise Nistrup
Abstract: Sugar beet ( Beta vulgaris ) is an important cash crop grown in temperate regions for the production of sugar. Fungal leaf diseases often infect the sugar beet crop during the season, causing significant yield reductions. This study aimed at investigating the effect of pre-symptomatic and well-timed fungicide treatments on disease control, yield, and economic profitability. Sixteen field trials were carried out between 2013 and 2016, showing sugar yield increases following fungicide applications in the range of 2–25%, depending on the disease severity and variety. Powdery mildew ( Erysiphe betae ) and beet rust ( Uromyces betae ) mainly had a significant impact on the sugar yield. Attacks of ramularia leaf spot ( Ramularia beticola ) and cercospora leaf spot ( Cercospora beticola ) were negligible. The impact from different timings and intensities of control measures was compared using two to five applications with a mixture of epoxiconazole + pyraclostrobin. Data did not show a clear advantage of fungicide sprays applied before visible symptoms or higher fungicide inputs used sugar yields. The yield improvement was only significant in one out of 16 cases. The economic return was highest in year with high disease pressure and for more powdery mildew-susceptible cultivars. Different spray intensities showed no economic difference on average. In conclusion, these field trials confirmed that the common practice of two to three applications per year is preferable to more intense spray programs. Scouting the crop during the season for fungal disease and spraying according to the disease pressure can help to minimize fungicide applications. Highlights: The application of fungicides increases yields significantly in the presence of fungal attacks. Powdery mildew and beet rust are the most widespread diseases in Denmark. Disease severity varies between sites, years, and cultivars. Presymptomatic fungicide treatments do not increase yields significantly and do not provide a higher economic return. Current IPM practices with a threshold identified by disease assessments work well.